Turkey's Interests in Maintaining Diplomatic Relations With Russia Over Conflict in Iblid, Syria year 2019 - Ningsih, Ida Ayu Tirta Purnama; Kurnia Putri, Penny; Intan Parameswari, Anak Agung Ayu (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 2 (2024): JURNAL DIKSHI, 2024)
Abstract This study aims to describe Turkiye's interests in establishing relations with Russia amid conflict tensions in the Idlib region, Syria in 2019. In the Sochi Agreement (2018), Turkey and Russia agreed to secure the Syrian situation, and make the Idlib region a demilitarized zone. However, Russia violated the agreement by carrying out air strikes in the region, thus endangering Turkiye's security stability. In response to this, Turkey actually took diplomatic steps against Russia through a ceasefire agreement in 2020. This study was analyzed qualitatively using the concepts of National Interest and Neoclassical Realism. The data interpretation process is carried out by collecting supporting data such as; data tables, graphs, and images. The data is then used as a reference to support the researcher's hypothesis. The researcher then found an answer that the interests that underlie Turkey's policy to maintain relations with Russia in the midst of the conflict situation in Idlib are economic interests related to Turkiye's dependence on export and import goods, interests in Russia's role in supporting revenues from Turkish tourism, Turkiye's energy interests which are still dependent on Russia, as well as Turkiye's defense and security interests which are unable to accommodate the surge in refugees from Syria.   Keywords :    Syrian Conflict, national Interest, Sochi Agreement, Neoclassical Realism, Turkey-Russia